Subacute Thyroiditis and Graves’ Disease Possibly Associated with Sars-CoV-2 Infection: Presentation of Two Cases and Review of the Current Data - Çelik, Özlem; Anaforoğlu, İnan (European Journal of Therapeutics, 2022)
The severe acute respiratory syndrome coronavirus 2 has been identified as the cause of a pandemic of respiratory illness in Wuhan, China. Coronavirus disease 2019 may cause mild disease with nonspecific signs and symptoms such as fever, cough, myalgia, and fatigue or severe pneumonia with respiratory failure and sepsis. It is not clear whether coronavirus disease 2019 has an effect on the thyroid gland. Evidence support that patients with coronavirus disease 2019 who are followed up in the intensive care unit may develop temporary thyroid dysfunction as non-thyroidal illness syndrome. Until now, 22 cases of subacute thyroiditis and 5 Graves’ diseases potentially related to severe acute respiratory syndrome coronavirus 2 infection have been presented in the literature. Herein, we present 2 cases with subacute thyroiditis and Graves’ diseases potentially related to severe acute respiratory syndrome coronavirus 2 infection in the context of the review of the literature. Physicians should be aware of the possible relationship between thyroid dysfunction and coronavirus disease 2019.